2022
DOI: 10.20473/jn.v17i1.24539
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between parental communication pattern, self-esteem, and moral disengagement with cyberbullying behavior in early adolescents: A cross-sectional study

Abstract: Introduction: Cyberbullying has become a new case in young millennials that can lead to being a serious problem if it is not faced properly. Many cases cannot be resolved because the victims did not tell the truth clearly to their parents and teachers. It may cause a lack of self-esteem among the students and also make the perpetrator become morally disengaged. The purpose of this study was to identify the correlation between parental communication patterns, moral disengagement, and self-esteem with cyberbully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…The finding on the positive impacts of social media on students' moral disengagement behavior is also supported in literature. For example, the current research outcome supports the finding made by Octavia et al, (2022) 2021) also disclosed that there is a significant relationship between moral development and dark triad influence on social media intent. This is also supported by the Fissel et al, (2021) findings which showed that cyber stalking perpetration among young adults significantly affects self-control and moral disengagement behavior.…”
Section: Discussion Of Findingssupporting
confidence: 87%
“…The finding on the positive impacts of social media on students' moral disengagement behavior is also supported in literature. For example, the current research outcome supports the finding made by Octavia et al, (2022) 2021) also disclosed that there is a significant relationship between moral development and dark triad influence on social media intent. This is also supported by the Fissel et al, (2021) findings which showed that cyber stalking perpetration among young adults significantly affects self-control and moral disengagement behavior.…”
Section: Discussion Of Findingssupporting
confidence: 87%